Development of Intensive Apprenticeship Models for Accelerating Certification - Isnandar, Isnandar; Suwarno, Eko; Ariestadi, Dian; Umniati, B. Sri; Al Ansyorie, Mohammad Musthofa (Fakultas Teknik Universitas Negeri Malang, 2021)
As a consequence of the rapid development of infrastructures, there is a scarcity of availability of skilled labor in construction services, so efforts are needed to accelerate the preparation of experts in the field of construction services. Intensive apprenticeship pattern is a program to accelerate the preparation of construction service workers in increasing the relevance of higher education to the world of work as a purpose in this study. Data analysis used comparative analysis and descriptive statistics. The results of the study show that the existing pattern of internship in the field carried out by the sample universities is that there are two things that have not been widely implemented, namely the provision of insurance and special facilities. While other items related to the implementation of internships have a percentage of more than 50 percent. The apprenticeship patterns that can be implemented include through the process of collaboration, socialization, participant registration, self assessment, matriculation, implementation of internships, appraisal, and granting certificates from the Construction Services Business Entity (CSBE/ BUJK). Whereas Certification is carried out in general through Pre-Internship, Internships, Judicium, Post-Judiciary, Graduation and Certification of Young Experts.